2011
DOI: 10.4161/auto.7.3.14046
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin-binding adaptor proteins p62/SQSTM1 and NDP52 are recruited independently to bacteria-associated microdomains to target Salmonella to the autophagy pathway

Abstract: Autophagy is an innate immune defense against bacterial invasion. Recent studies show that two adaptor proteins, p62 and NDP52, are required for autophagy of the bacterial pathogen Salmonella enterica serovar Typhimurium (S. typhimurium). However, it is not known why two different adaptors are required to target the same bacterial cargo to autophagy. Here we show that both adaptors are recruited to bacteria with similar kinetics, that they are recruited to bacteria independently of each other, and that depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
173
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(188 citation statements)
references
References 18 publications
14
173
1
Order By: Relevance
“…It can bind both LC3 and ubiquitinated proteins through the LC3 interaction region and ubiquitin-associated domain, respectively (11,14). NDP52 is another cargo marker that drives certain bacteria to the autophagy machinery (9,41). In this study, we found that NDP52 facilitates autophagy uptake of B. cepacia in ⌬F508 macrophages but not in WT cells.…”
Section: Discussionsupporting
confidence: 48%
“…It can bind both LC3 and ubiquitinated proteins through the LC3 interaction region and ubiquitin-associated domain, respectively (11,14). NDP52 is another cargo marker that drives certain bacteria to the autophagy machinery (9,41). In this study, we found that NDP52 facilitates autophagy uptake of B. cepacia in ⌬F508 macrophages but not in WT cells.…”
Section: Discussionsupporting
confidence: 48%
“…1B,C). A possible explanation for this observation is that p62 and NBR1 mediate independent but parallel peroxisome degradation pathways, like that found with NDP52 and p62 in S. typhimurium (Cemma et al, 2011). Conversely, both may be involved in the same pathway but at different stages.…”
Section: Nbr1 Is Required For the Turnover Of Peroxisomesmentioning
confidence: 87%
“…Interestingly, the colocalization of p62 with NBR1 was only partial as there were distinct NBR1 and p62 structures juxtaposed to each other around peroxisomes. These structures may be analogous to the microdomains formed by the autophagy receptors p62 and NDP52 around Salmonella inside autophagosomes (Cemma et al, 2011;Mostowy et al, 2011;Zheng et al, 2009). However, the nature of these microdomains is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore Listeria evades both septin caging and autophagy via its surface expression of ActA (11). Given these fundamental differences between Shigella and Listeria, it is clear that in-depth investigation of these two bacteria will help to describe precisely the coordination among actin, septin, and selective autophagy.The role of p62 and/or NDP52 in selective autophagy of Salmonella enterica serovar Typhimurium (S. typhimurium) has recently been characterized (9,14,15). It has been proposed that p62 and NDP52 act independently to drive efficient bacterial autophagy of S. typhimurium within Salmonella-containing vacuoles (15).…”
mentioning
confidence: 99%